Plastome Evolution in the Hyperdiverse Genus Euphorbia (Euphorbiaceae) Using Phylogenomic and Comparative Analyses: Large-Scale Expansion and Contraction of the Inverted Repeat Region - Wei, Neng; Pérez-Escobar, Oscar A.; Musili, Paul M.; Huang, Wei-Chang; Yang, Jun-Bo; Hu, Ai-Qun; Hu, Guang-Wan; Grace, Olwen M.; Wang, Qing-Feng (Frontiers in Plant Science, 2021)
With c. 2,000 species, Euphorbia is one of the largest angiosperm genera, yet a lack of chloroplast genome (plastome) resources impedes the better understanding of its evolution. In this study, we assembled and annotated 28 plastomes from Euphorbiaceae, of which 15 were newly sequenced. Phylogenomic and comparative analyses of 22 plastome sequences from all four recognized subgenera within Euphorbia revealed that plastome length in Euphorbia is labile, presenting a range of variation c. 42 kb. Large-scale expansions of the inverted repeat (IR) region were identified, and at the extreme opposite, the near-complete loss of the IR region (with only 355 bp left) was detected for the first time in Euphorbiaceae. Other structural variations, including gene inversion and duplication, and gene loss/pseudogenization, were also observed. We screened the most promising molecular markers from both intergenic and coding regions for phylogeny-based utilities, and estimated maximum likelihood and Bayesian phylogenies from four datasets including whole plastome sequences. The monophyly of Euphorbia is supported, and its four subgenera were recovered in a successive sister relationship. Our study constitutes the first comprehensive investigation on the plastome structural variation in Euphorbia and it provides resources for future phylogenetic research in the genus, facilitating further studies on its taxonomy, evolution, and conservation.